Improved method for image security based on chaotic-shuffle and chaotic-diffusion algorithms - Sanjeev Sharma; Tarun Kumar; Ravi Dhaundiyal; Amit Kumar Mishra; Nitin Duklan; Ashish Maithani (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, we propose to enhance the security performance of the color image encryption algorithm which depends on multi-chaotic systems. The current cryptosystem utilized a pixel-chaotic-shuffle system to encode images, in which the time of shuffling is autonomous to the plain-image. Thus, it neglects to the picked plaintext and known-plaintext attacks. Also, the statistical features of the cryptosystem are not up to the standard. Along these lines, the security changes are encircled to make the above attacks infeasible and upgrade the statistical features also. It is accomplished by altering the pixel-chaotic-shuffle component and including another pixel-chaotic-diffusion system to it. The keys for diffusion of pixels are extracted from the same chaotic arrangements created in the past stage. The renovation investigations and studies are performed to exhibit that the refreshed version of cryptosystem has better statistical features and invulnerable to the picked plaintext and known plaintext attacks than the current algorithm.